CURRENT OPINION ON TAXONOMY, MORPHOLOGICAL, AND FUNCTIONAL PROPERTIES OF BIFIDOBACTERIA - YULIYА V. Zakharova; LYUDMILA A. Levanova (Фундаментальная и клиническая медицина)
Here we present current information on the taxonomy of bifidobacteria, which is based on their phenotypic, genetic and phylogenetic characteristics. We also provide the data on newly discovered and reclassified species and subspecies of bifidobacteria. Furthermore, we consider the composition of the Bifidobacteriaceae family. This lecture summarizes the general data on morphology, cell wall structure, genome, and extrachromosomal inheritance in bifidobacteria. Particular attention is given to pili-like structures and saccharolytic enzymes responsible for adhesion. We then review key energy sources of bifidobacteria, their growth conditions, and specific enzymes involved in the fermentation of hexoses. Finally, we discuss ecological aspects related to bifidobacteria.